The Necessity of Dissection of No. 14 Lymph Nodes to Patients With Pancreatic Ductal Adenocarcinoma Based on the Embryonic Development of the Head of the Pancreas - Qian, Lihan; Xie, Junjie; Xu, Zhiwei; Deng, Xiaxing; Chen, Hao; Peng, Chenghong; Li, Hongwei; Chai, Weimin; Xie, Jing; Wang, Weishen; Shen, Baiyong (Frontiers in Oncology, 2020)
Objectives: Pancreaticoduodenectomy (PD) followed by lymphadenectomy is performed for patients with pancreatic ductal adenocarcinoma (PDAC) located in the head of the pancreas. Since the head of the pancreas could be divided into dorsal or ventral primordium in relation to embryonic development, the metastasis of lymph node (LN) may differ. In this retrospective study, we evaluated the impact of extended or standard LN dissection for PDAC located in ventral or dorsal primordia of the pancreatic head. Methods: From February 2016 to November 2018, 178 patients underwent PD for PDAC were enrolled at Pancreatic disease center, Ruijin Hospital Shanghai Jiaotong University School of Medicine. According to the tumor location and the range of LN dissection, all patients were divided into 3 groups: ventral primordium with extended lymphadenectomy (VE group), ventral primordium with standard lymphadenectomy (VS group) and dorsal primordium with extended lymphadenectomy (DE group). Clinical and pathological features were retrospectively analyzed, as well as the long-term survival outcomes. Results: More patients in VE group were detected with metastasis in lymph nodes around superior mesenteric artery (LN14) than those in DE group (LN along right side of superior mesenteric artery (LN14ab): 22.9% vs 5.9%, p=0.005; (LN along left side of superior mesenteric artery (LN14cd): 10.0% vs 0.0%, p=0.022). LN14 was involved in more patients in VE group than in VS group (22.9% vs 5.0%, p=0.015). For IIb stage patients in VE group, the overall survival time (18.3 months vs 9.3 months, p＜0.001) and disease-free survival time (12.2 months vs 5.1 months, p=0.045) were longer in those with LN14cd (-) than those with LN14cd (+). Conclusion: This study suggested that patients with PDAC located in the ventral head of the pancreas had higher risk of LN14 involvement compared with those at dorsal. Thus a thorough dissection of LN14 in PDAC located in the ventral head of the pancreas is recommended to optimize the regional extended lymphadenectomy.